Criminal Policy in The Formulation of Article 523 Paragraphs 1 & 2 of Election Law No. 7 of 2017 Related to DPRD Elections - Mahesa, Berlian; Panjaitan, Saut P; Achmad, Ruben (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Violations before elections committed by non-formal actors in mobilizing the masses are an interesting mechanism to discuss. This study aims to explain related to criminal policies against electoral criminal offenses in Article 523 paragraph 1 and Article 523 paragraph 2, factors that influence criminal policies in the implementation of Article 523 paragraphs 1 and 2 and criminal policies against electoral crimes Article 523 paragraph 1 and Article 523 paragraph 2 in the future. Research methods used in empirical normative research. The results of this study show that: First, criminal policies against electoral criminal violations in Article 523 paragraph 1 and Article 523 paragraph 2 can be pursued in various ways. Several ways that can be done as a form of criminal policy in solving the problem of electoral criminal violations in Article 523 paragraph 1 and Article 523 paragraph 2 include using penal methods, without using penal means (prevention without punishment) and efforts to form public opinion. Second, several factors that influence criminal policy in the implementation of Article 523 paragraphs 1 and 2 include the following: ineffective judicial implementation, unauthoritative laws, uncoordinated supervision and prevention and lack of participation from the public. Third, criminal threats in the electoral law were revised by changing criminal sanctions to administrative sanctions. Administrative sanctions are considered the most effective where the provision of sanctions will facilitate the enforcement of these norms and in turn we will see the usefulness or results of these laws and regulations. In addition, the inclusion of sanctions is also an effort to make someone comply with the provisions of laws and regulations.